The influence of hydraulic characteristics on algal bloom in three gorges reservoir, China: A combination of cultural experiments and field monitoring. (1st March 2022) - Yang, Zhengjian; Wei, Chenyu; Liu, Defu; Lin, Qicai; Huang, Yuling; Wang, Congfeng; Ji, Daobin; Ma, Jun; Yang, Hong
Highlights: Effects of flow velocity, retention time, and stratification on algal growth were experimented comparatively. Ratio of mixing depth and euphotic layer (Z m/Z e) was used to assess the risk of algal bloom. Flow velocity and retention time were not direct hydrodynamic parameters to drive the algal bloom in the TGR. Z m/Z e >2.8 was proposed to restrain algal bloom in the TGR. Abstract: It is essential to understand the mechanism of algal bloom and develop effect measures to control the hazard in aquatic environment, such as large reservoirs. In this study, a series of experiments, along with field observation from 2007 to 2016, were carried out to identify the hydrodynamic parameters that drive the algal bloom in the Three Gorges Reservoir (TGR), China, and their threshold values were determined. The results show that algae concentration was markedly diluted with a short retention time, and the threshold value of the retention time to avoid algal bloom was approximately less than 3 days. With strong stratification, the algae concentration was able to approach to the level of algal bloom in 10 days, even when the water temperature is lower than 12 °C. The ratio of mixing depth to euphotic depth (Z m/Z e) had significant negative correlations with both algae concentration and algae specific growth rate (SGR). The field monitoring data indicated that Z m/Z e is an important hydrodynamic parameter which sensitively affects algae growth and concentration. This study made the first attempt to determine Z m/Z e >2.8 to restrain algal bloom in the TGR. Our findings shed light on the influence of critical depth on the algal bloom in the TGR, and the results can serve to control algal bloom in reservoirs through discharge operation. Graphical abstract: Image, graphical abstract